Propaedeutic Study of Biocomposites Obtained With Natural Fibers for Oceanographic Observing Platforms - Aracri, Simona; Contardi, Marco; Bayer, Ilker S.; Zahid, Muhammad; Giorgio-Serchi, Francesco; Stokes, Adam A. (Frontiers in Marine Science, 2021)
In response to the pervasive anthropogenic pollution of the ocean, this manuscript suggests the use of biodegradable elastomers in marine applications. The present study characterises 25 samples of highly biodegradable polymers, obtained blending a base elastomer with natural fibres. Mechanical analysis and Scanning Electron Microscope imaging, reveal how base polymers behave differently depending on the plant fibre chosen, on the external forcing - exposure to water - and on the doses that constitute the final biocomposite. Results suggest that EcoflexTM 00-30 and EcoflexTM 00-50, mixed with potato starch, perform best mechanically, maintaining up to 70% of their maximum tensile strain. Moreover early signs of degradation are visible on polysiloxane rubber blended with 50% vegetable fibres after 19 hours in distilled water. Analyses demonstrate that highly biodegradable elastomers are good candidates to satisfy the requirements of aquatic devices. Furthermore, the discussed materials can improve the dexterity and biodegradability of marine technology.